TMAO Promotes NLRP3 Inflammasome Activation of Microglia Aggravating Neurological Injury in Ischemic Stroke Through FTO/IGF2BP2 - Ge P; Duan H; Tao C; Niu S; Hu Y; Duan R; Shen A; Sun Y; Sun W (Dove Medical Press, 2023)
Pengxin Ge,1,* Huijie Duan,2,* Chunrong Tao,3,* Sensen Niu,4 Yiran Hu,5 Rui Duan,6 Aizong Shen,7 Yancai Sun,1 Wen Sun3 1Department of Pharmacy, Anhui Provincial Cancer Hospital, The First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, 230031, People's Republic of China; 2School of Basic Medicine and Clinical Pharmacy, China Pharmaceutical University, Nanjing, 210009, People's Republic of China; 3Stroke Center and Department of Neurology, The First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, 230001, People's Republic of China; 4Digestive System Department, The Second Affiliated Hospital of Anhui Medical University, Hefei, 230601, People's Republic of China; 5Department of Scientific Research, The First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, 230001, People's Republic of China; 6Department of Neurology, Nanjing First Hospital, Nanjing Medical University, Nanjing, 210006, People's Republic of China; 7Department of Pharmacy, The First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, 230001, People's Republic of China*These authors contributed equally to this workCorrespondence: Wen Sun; Aizong Shen, Email sunwen_medneuro@163.com; 1649441800@qq.comObjective: Stroke is a kind of cerebrovascular disease with high mortality. TMAO has been shown to aggravate stroke outcomes, but its mechanism remains unclear.Materials and Methods: Mice were fed with 0.12% TMAO for 16 weeks. Then, mice were made into MCAO/R models. Neurological score, infarct volume, neuronal damage and markers associated with inflammation were assessed. Since microglia played a crucial role in ischemic stroke, microglia of MCAO/R mice were isolated for high-throughput sequencing to identify the most differentially expressed gene following TMAO treatment. Afterward, the downstream pathways of TMAO were investigated using primary microglia.Results: TMAO promoted the release of inflammatory cytokines in the brain of MCAO/R mice and promoted the activation of OGD/R microglial inflammasome, thereby exacerbating ischemic stroke outcomes. FTO/IGF2BP2 inhibited NLRP3 inflammasome activation in OGD/R microglia by downregulating the m6A level of NLRP3. TMAO can inhibit the expression of FTO and IGF2BP2, thus promoting the activation of NLRP3 inflammasome in OGD/R microglia. In conclusion, these results demonstrated that TMAO promotes NLRP3 inflammasome activation of microglia aggravating neurological injury in ischemic stroke through FTO/IGF2BP2.Conclusion: Our results demonstrated that TMAO promotes NLRP3 inflammasome activation of microglia aggravating neurological injury in ischemic stroke through FTO/IGF2BP2. These findings explained the molecular mechanism of TMAO aggravating ischemic stroke in detail and provided molecular mechanism for clinical treatment.Keywords: stroke, TMAO, NLRP3 inflammasome, OGD/R, microglia, FTO, IGF2BP2